Thermal behaviour of α-hydroxyisobutyric acid, sodium α-hydroxyisobutyrate and its compounds with some bivalent transition metal ions - Gomes, D. J C [UNESP]; Caires, F. J. [UNESP]; Lima, L. S. [UNESP]; Gigante, A. C. [UNESP]; Ionashiro, Massao [UNESP] (Elsevier, 2013)
Synthesis, characterization and thermal decomposition of bivalent transition metal α-hydroxyisobutyrates, M(C4H7O 3)2·nH2O (M = Mn(II), Fe(II), Co(II), Ni(II), Cu(II), Zn(II)), as well as the thermal behaviour of α-hydroxyisobutyric acid and its sodium salt were investigated employing simultaneous thermogravimetry and differential scanning calorimetry (TG-DSC), infrared spectroscopy (FTIR), TG-DSC coupled to FTIR, elemental analysis and complexometry. All the compounds were obtained as dihydrated, except the copper one which was obtained in the anhydrous state. The thermal decomposition of the anhydrous compounds occurs in a single or two steps and the final residue up to 235 C (Mn), 300 C (Fe), 305 C (Co), 490 C (Ni), 260 C (Cu) and 430 C (Zn) is Mn2O3, Fe2O3, Co3O 4, NiO, CuO and ZnO, respectively. The results also provided information concerning the ligand's denticity and identification of the gaseous products evolved during the thermal decomposition of these compounds. Copyright © 2013 Published by Elsevier B.V. All rights reserved.
Keywords: α-Hydroxyisobutyrate; Bivalent transition metals; Evolved gases; Thermal decomposition; Thermal stability; Anhydrous compounds; Complexometry; Evolved gas; Gaseous products; Information concerning; Sodium salt; Thermal behaviours; Copper; Decomposition; Differential scanning calorimetry; Infrared spectroscopy; Iron compounds; Manganese; Metal ions; Nickel; Pyrolysis; Thermodynamic stability; Thermogravimetric analysis; Zinc; Zinc compounds; Zinc oxide; Cobalt compounds